Soil test and targeted yield based primary nutrient management of marigold (Tagetus patula) in an Inceptisol - DURGA, M LAKSHMI; RAJU, D V S; PANDEY, R N; SINGH, KANWAR PAL; KUMAR, PRABHAT; PANDEY, RENU; GOPALAKRISHNAN, S; CHANDRA, SURESH (The Indian Journal of Agricultural Sciences, 2017)
Field experiments was conducted on marigold (Tagetus patula L.) var. Pusa Arpita during 2014-16 using Ramamoorthy’s inductive methodology for the quantification of soil test and crop requirement based integrated fertilizer prescription of primary nutrients for targeted yield of marigold at ICAR-Indian Agricultural Research Institute, New Delhi. The results of the experiment indicated that 0.46 kg N, 0.07 kg P and 0.49 kg K were required to produce one quintal of marigold flowers in Inceptisols of New Delhi. The contributions (%) from soil, fertilizer nutrients and FYM were found to be 46.33, 45.53 and 21.60 for N; 59.62, 20.42 and 8.87 for P and 47.22, 85.71 and 6.11 for K, respectively. The fertilizer prescription equations were developed and nomograms were formulated based on the equations for a range of soil test values and desired yield targets of marigold. Under NPK + 10 tonnes/ha FYM, 9.3, 10.17, and 3.09 kg/ha of fertilizer N, P2O5 and K2O could be saved for attaining targeted yield of 30 tonnes/ha as compared to NPK fertilizer alone at a given soil test values of 100, 4 and 100 kg of N, P2O5 and K2O, respectively.